Assessment of High Serum Cystatin C as an Early Marker of Renal Impairment in Pre Eclampsia - Ferdoues, Tahsnin; Akhtar, Nahreen; Arbab Sarker, Mohammad; Aziza Wahid, Ummee; Akter, Masuma; Tabassum, Mishkat (Medicine Today, 2024)
Introduction: Preeclampsia is the most common medical complication during pregnancy and one of the leading causes of maternal and perinatal morbidity and mortality in Bangladesh. Kidney has role in both adaptive physiology of normal pregnancy and in pathophysiology of preeclampsia. Among the new biomarkers, serum Cystatin C can reliably reflect the GFR in both healthy and hypertensive pregnant women. It is important to evaluate the diagnostic efficiency of Cystatin C as a marker of renal function in preeclampsia. Aim: To assess high serum Cystatin C level as an early marker of renal impairment in pre-eclamptic patients. Materials and Methods: From March, 2021 to February, 2022 (A total of 12 months) a cohort study was conducted among 66 pregnant women, aged 18 to 40 years with pre-eclampsia and normal serum creatinine (0.5-0.8mg/dl) at their 20-28 weeks of gestation attending the antenatal clinic and admitted in the Department of Feto maternal Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, selected by non random purposive and convenient sampling. Results: Out of 66 respondents, final analysis was done with 62 patients. Among 62 study samples, 76% patients had “High Cystatin C” level that was greater than 0.84 and renal impairment developed in 15% pregnant women. Majority of the participants were in 25-30 age groups (46.8%). The mean serum creatinine level of the pregnant women increased throughout follow up and it was statistically significant (p<0.05) in both cases. No significant difference was found between serum Cystatin C in renal impaired and normal renal function pre eclampsia patients at a cut off value of 0.84. ROC analysis of serum Cystatin C level for detection of renal impairment among Pre eclamptic patients found a cut-off value of ≥1.49 showed the highest Youden index of 0.721. The sensitivity, specificity, PPV, NPV and accuracy of serum Cystatin C were 77.78%, 94.34%, 70.00%, 96.15% and 91.94%. Conclusion: Higher Cystatin C level in pre-eclampsia reflected renal impairment at an early stage even before conventional marker like serum creatinine raise. The diagnostic efficiency of Cystatin C as a marker of renal function in pre eclampsia can be used to reduce maternal morbidity and mortality of Bangladesh. Medicine Today 2023 Vol.36 (1): 12-16